Teriflunomide: A possible effective drug for the comprehensive treatment of COVID-19 - Amgad M. Rabie (Elsevier, 2021)
The coronavirus disease 2019 (COVID-19) pandemic has undoubtedly become a global crisis. Consequently, discovery and identification of new or known potential drug candidates to solve the health problems caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) have become an urgent necessity. This current research study sheds light on the possible direct repurposing of the antirheumatic drug teriflunomide to act as an effective and potent anti-SARS-CoV-2 agent. Herein, an interesting computational molecular docking study of teriflunomide, to investigate and evaluate its potential inhibitory activities on the novel coronaviral-2 RNA-dependent RNA polymerase (nCoV-RdRp) protein, was reported. The docking procedures were accurately carried out on nCoV-RdRp (with/without RNA) using the COVID-19 Docking Server, through adjusting it on the small molecule docking mode. Remdesivir and its active metabolite (GS-441524) were used as the active references for the comparison and evaluation purpose. Interestingly, the computational docking analysis of the best inhibitory binding mode of teriflunomide in the binding pocket of the active site of the SARS-CoV-2 RdRp revealed that teriflunomide may exhibit significantly stronger inhibitory binding interactions and better inhibitory binding affinities (teriflunomide has considerably lower binding energies of −9.70 and −7.80 ​kcal/mol with RdRp-RNA and RdRp alone, respectively) than both references. It was previously reported that teriflunomide strongly inhibits the viral replication and reproduction through two mechanisms of action, thus the results obtained in the present study surprisingly support the double mode of antiviral action of this antirheumatic ligand. In conclusion, the current research paved the way to practically prove the hypothetical theory of the promising abilities of teriflunomide to successfully attack the SARS-CoV-2 particles and inhibit their replication in a triple mode of action through integrating the newly-discovered nCoV-RdRp-inhibiting properties with the previously-known two anticoronaviral mechanisms of action. Based on the previous interesting facts and results, the triple SARS-CoV-2/sextet COVID-19 attacker teriflunomide can further undergo in vitro/in vivo anti-COVID-19 assays together with preclinical/clinical studies and trials in an attempt to evaluate and prove its comprehensive pharmacological activities against the different SARS-CoV-2 strains to be effectively used in COVID-19 therapy in the very near future.